AN ERROR ANALYSIS OF NON- ENGLISH STUDENTS DEPARTMENT IN ANSWERING LISTENING SECTION IN TOEFL - Muhammad Soali; Tri Pujiani (J-LEE - Journal of Law, English, and Economics, 2020)
Abstract Several universities in Indonesia apply the TOEFL test as one of the graduation requirements by considering the importance of mastering English for students, either continuing higher education levels or as a requirement for applying for jobs. Each university has a different standard score as a requirement for graduation. Some universities use the TOEFL test to measure the ability of their students in English. In practice, many students experience difficulties. This study aims to determine the most difficult part of the TOEFL listening comprehension and to determine the factors that make it difficult for students to do listening. 25 seventh semester students of Nursing Study Program participated in this study selected by using random sampling techniques. Descriptive qualitative method was used in this research. The results of this study indicate that the difficulties experienced by students based on the content of their listening material are difficulties in choosing synonyms of keywords, double negative expressions, idioms, main idea of ​​the paragraph, and detailed information. Difficulties related to listeners are excessive anxiety, difficulty in concentration while listening, difficulties regarding vocabulary meaning, difficulty in drawing conclusions on conversations. Meanwhile, the factors that affect students' difficulty in doing TOEFL listening comprehension test questions are low level of self-confidence, low mastery of English vocabulary, low mastery of the skills tested on the TOEFL test, inability in time management, and lack of intensity of practice on the TOEFL test. Kata Kunci: TOEFL listening, listening difficulty, listening comprehension, listening test. Abstrak Sebagian universitas di Indonesia menerapkan tes TOEFL sebagai salah satu persyaratan kelulusan dengan pertimbangan pentingnya penguasaan Bahasa Inggris untuk mahasiswa. Beberapa universitas menggunakan tes TOEFL untuk mengukur kemampuan siswanya dalam Bahasa Inggris. Dalam praktiknya mahasiwa mengalami kesulitan, terutama pada listening comprehension. Penelitian ini bertujuan untuk mengetahui elemen tersulit dari TOEFL listening comprehension dan mengetahui faktor yang membuat mahasiswa kesulitan dalam mengerjakan listening comprehension. 25 mahasiswa semester tujuh Program Study S1-Keperawatan menjadi partisipan dalam penelitian ini dengan menggunakan teknik random sampling. Metode qualitative deskriptif digunakan dalam penelitian ini. Hasil dari penelitian ini menunjukkan bahwa kesulitan yang dialami siswa berdasarkan konten listening material nya adalah kesulitan dalam memilih synonym of keyword, double negative expressions, idioms, main idea of the paragraph, dan detail information. Kesulitan yang berkaitan dengan listener yaitu kecemasan yang berlebihan, kesulitan berkonsentrasi saat mendengarkan, kesulitan perihal makna vocabulary, kesulitan mengambil kesimpulan percakapan. Sedangkan faktor yang mempengaruhi mahasiswa kesulitan dalam mengerjakan soal test TOEFL listening comprehension yaitu rendahnya tingkat kepercayaan diri, rendahnya penguasaan vocabulary Bahasa Inggris, rendahnya penguasaan terhadap skills yang diteskan dalam tes TOEFL, ketidakmampuan dalam manajemen waktu, dan minimnya intensitas latihan mengerjakan test TOEFL. Keywords: listening, kesulitan listening, listening comprehension, test listening